DECIDING BETWEEN RAILWAY AND ROAD TRANSPORT OF DANGEROUS ITEMS WITH RESPECT TO THE LEVEL OF CUSTOMER SERVICES - Vlčková, Vladimíra; Lošťáková, Hana; Bártová, Kristýna (STEF92 Technology Ltd., 2016)
In the present highly competitive dynamic environment, significant competitiveness factors include the level of services the customer is provided with. Their important components include services connected with delivery, from which it is particularly transport what has, among others, a significant impact on the date of delivery to the customer, its flexibility and reliability. However, transport often represents, compared to the other logistics activities, the largest independent cost item. Therefore, companies try to decrease this cost by choosing the optimum way of transport. However, transport also has a significant impact on the environment. The transportation sector accounts globally for 24 per cent of CO2 emissions, of which 40 per cent represents the freight traffic. And by 2050, freight transport performance is expected to have grown by almost three quarters. The most widely used ways of transport in Central Europe are road and railway transport. A lot of companies thus decide, when choosing the way of transport, between these two alternatives. Therefore, this paper specifies and evaluates, on the basis of the outcomes of a conducted analysis and assessment of the process of transport of dangerous items, the factors affecting the choice of transport within implementation of a business case in a selected chemical industry company. The analysed data were obtained through our own survey conducted using the method of in-depth interviews based on an interviewing scenario with selected employees of the company responsible for transport and sale. The benefit of the paper can be seen in identification of the factors that can, while respecting the customer requirements concerning the provided services, support extended utilization of railway transport, which shows absolutely the lowest energy demand, and, at the same time, CO2 emissions of all the modes of transport.
ROZHODOVÁNÍ MEZI ŽELEZNIČNÍ A SILNIČNÍ PŘEPRAVOU NEBEZPEČNÝCH VĚCÍ S OHLEDEM NA ÚROVEŇ SLUŽEB ZÁKAZNÍKŮM
Keywords: DECIDING; RAILWAY TRANSPORT; ROAD TRANSPORT; DANGEROUS ITEMS; CUSTOMER SERVICES; Rozhodování; železniční přeprava; silniční přeprava; nebezpečné věci; služby zákazníkům